Learning The Effect of Basagran to The Paramagnitic Centres of Mammal's Blood - Berdiev Ural Buranovich; Bobomuratov Sardor Abdurasul o’g’li (Zien Journals, 2021)
The article studies the effect of pesticides in mammalian blood on free radicals and paramagnetic centers. We studied the effect of basagran on mammals, as well as free radicals formed in living organisms as a result of the combined action of basagran and nitrites. For the first time, an increase in the number of free radicals in the blood under the influence of basagran was revealed, and the effect of nitrites on the change in paramagnetic centers in the blood was also studied.
Keywords: pesticides; nitrate; blood; hemoglobin